The influence of profitability, asset tangibility, firm size, liquidity, and agency conflict toward capital structure on food and beverage companies listed in Indonesia stock exchange / Erika Jimena Arilyn. - Arilyn, Erika Jimena (Universiti Teknologi Mara, Selangor, 2020)
This study is conducted in order to know whether profitability, asset tangibility, firm size, iquidity, and agency conflict influence the capital structure. This study would also compare the result of the previous researchers within this research. Sample of this research is food and beverage companies that are listed in Indonesia Stock Exchange for period 2014 - 2017 and publish its annual report, which is available to be accessed by the public. The research method used in this paper is the quantitative method. Purposive sampling is used as a sampling technique, where nine companies met the criteria and were analyzed using descriptive statistic and panel data regression with a random effect model to test the hypotheses. Results of this study indicate that profitability, liquidity, and agency conflict influence the capital structure, while asset tangibility and firm size do not influence the capital structure.